Efektivitas Penggunaan Anggaran Dana Desa Terhadap Pembangunan Berkelanjutan Desa Lamantu Kabupaten Kepulauan Selayar - Rostini Hasanuddin; Jumiati Nurdin (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
The purpose of the study was to determine the effectiveness of using the village fund budget for sustainable development in Lamantu Village, Pasimarannu District, Selayar Regency. This type of descriptive research with a qualitative approach aims to provide a systematic, factual and accurate description of the analysis of reports on the use of village funds in sustainable development in Lamantu village. Location of Lamantu village, Pasimarannu sub-district, Selayar district and research time, September to October 2018. The independent variable is the use of the village fund budget (X). The dependent variable is Sustainable Development (Y). Observational data collection. The results showed that the effectiveness of the use of village funds in Lamantu village was quite good and in accordance with the needs of the community. development carried out based on the results of an agreement by mutual deliberation. with the use of funds for the administration of the Lamantu village government, this field requires funds of Rp.470.936,712 of the total budget provided. This field focuses more on personnel and operational expenditures as well as the Lamantu village administration system for the 2016 fiscal year. 64% of the total budget is used for development. as much as Rp.641,158,281 used for the construction or improvement of village roads, construction of concrete rebates, construction of educational infrastructure and construction of other facilities and infrastructure. the field of community development absorbs 3%, namely Rp. 82,371,000 with programs namely youth development and sports, arts and socio-culture, prevention of illegal logging and illegal fishing, reforestation at village level, and education of santri. In the field of community empowerment in Lamantu Village, a budget of 15% or around Rp. 237,809,228 carries out capacity building for Community Institutions/Groups, activities to improve malnutrition for toddlers, pregnant women and poor families, PKK mobilizing team activities, orientation activities for PPKBD and Sub PPKBD meetings , healthy Regency activities, and livestock/fishery/agriculture capacity building activities.